(untitled) (Research, Society and Development, 2022)
The objective of this work is to describe the chronic evolution of Chikungunya infection, its severity factors and its relationship with autoimmune diseases. The case report refers to an adult female patient diagnosed with rheumatoid arthritis (RA), who complained of pain in her wrists, knees, ankles and elbows, which worsened after the end of an acute case of Chikungunya and there was an increase in joint swelling and morning stiffness, without heat or erythema. It was observed that a mistaken diagnosis of RA was made in the patient, due to a similar clinic, which even showed positivity for rheumatoid factor (RF). Through the results of the exams, it was found that the patient did not have rheumatoid arthritis and that her treatment was inadequate for her real diagnosis, therefore, she did not obtain a satisfactory result. Therefore, the differential diagnosis and therapy of chronic Chikungunya should be kept in mind to facilitate the improvement of patients’ quality of life.